A POLÍCIA EM PAUTA: ANÁLISE DOS CRITÉRIOS DE NOTICIABILIDADE DAS CHAMADAS COM FOTO AGENDADAS NAS CAPAS DO JORNAL DA MANHÃ E DIÁRIO DOS CAMPOS EM 2014 - Kaliberda, Andressa (2015)
This Master thesis studies Media Agenda in Police pages in daily news in Ponta Grossa, Paraná, Brazil. The study analyzes the main news criteria that contribute to the agenda-setting of police content with photographs in the covers of Diário dos Campos and Jornal da Manhã, as well as the connection between text and photojournalistic image in this process. To do so, the sample consists on the first week of each even month in the year of 2014 in both newspapers. Enrolled in Line 2 of the Postgraduate Program in Journalism of Ponta Grossa State University, "Journalistic Processes and Social Practices", this investigation is grounded in the following concepts: Media Agenda, News Criteria and Police Journalism. The method used is the quantitative content analysis, with qualitative inferences. The news criteria present in texts and photos of the cover stories about police news, the space these stories occupy and the corresponding content, the format of the text publicized in inside pages that is linked to the cover and the main themes that appear in the cover are evaluated. The analysis identified a tendency of publishing themes coming from official releases and, in Jornal da Manhã, the use of cover stories for contents published in inside pages as notes. News-values that appeared the most are "proximity", "impact", "rarity", "surprise" and "tragedy/drama". With this study, it is intended to contribute academically to the comprehension of news criteria that guide Police Journalism, especially on what concerns the appreciation of said theme on the covers of regional papers headquartered in the country.